Improved Synthesis of 6-Azido-6-deoxy- and 6,6′-Diazido-dideoxy-α,α-trehaloses - Narouz, Mina R.; Soliman, Sameh E.; Bassily, Rafik W.; El-Sokkary, Ramadan I.; Nasr, Adel Z.; Nashed, Mina A. (Synlett, 2013)
An efficient synthesis of 6-azido-6-deoxy and 6,6′-diazido-dideoxy-α,α-trehalose derivatives was achieved by reaction of trifluoromethanesulfonic anhydride with partially trimethylsilylated heptakis- and hexakis-O-(trimethylsilyl)-α,α-trehalose in the presence of pyridine and 4-(N,N-dimethylamino)pyridine. Displacement with azide and desilylation afforded the title compounds, which represent potential precursors for the corresponding 6-amino- and 6,6′-diamino-trehaloses.
Keywords: carbohydrate chemistry; regioselectivity; azides; protecting groups